Face Detection Using Backpropagation Neural Networks - Anifuddin Azis; Muhamad Haikal (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2007)
AbstractThis paper summarizes a research effort in human face detection. A system to locate human faces in images, especially when used as a front-end for a human face identification system, could have many applications in the law enforcement and security professions. The approach presented here is a hybrid system using an edge deletion preprocessor and back-propagation neural networks. The method proposed successfully detected multiple faces. The results obtained are reported along with a discussion for improving the system.Keywords: Backpropagation neural networks, Edge Detection